Microalgae of pineapple [Ananas comosus (L.) Merr] Phytotelmata from Calauan, Laguna (Philippines) - Arguelles, Eldrin DLR. (2020)
Phytotelmata are a unique habitat for the existence of new and rare species of microalgae. In the Philippines, no comprehensive study was documented regarding the diversity of microalgae on bromeliad phytotelmata. This study provides the first floristic survey that presents the taxonomy and species composition of phytotelm microalgae associated with bromeliad tanks of pineapple [Ananas comosus (L.) Merr] from Calauan, Laguna. A total of 15 algal taxa were taxonomically identified from the collected samples, of which six species (five genera) are classified as members of Cyanophyceae, four species (three genera) belong to Zygnematophyceae, three species (three genera) to Chlorophyceae, and one species (one genus) each for Euglenophyceae and Klebsormidiophyceae. The study reports an additional of nine species (Phacus monilatus, Monoraphidium lunare, Coelastrum proboscideum, Klebsormidium flaccidum, Cosmarium granatum, Cosmarium contractum var. rotundatum, Phormidium breve, Arthrospira jenneri, and Chroococcus subnudus) as new records in the global inventory list of phytotelm microalgae and 13 new taxa as additional records of microalgae in phytotelm microhabitat of Asia. Also, the occurrence of a rare photosynthetic euglenoid [Phacus monilatus (Stokes) Lemmerman] and a green microalga, [Monoraphidium lunare Nygaard, J. Komárek, J. Kristiansen, & O.M. Skulberg] are described for the first time in the Philippines. Diagnostic descriptions and keys are presented to distinguish the different species of phytotelm algae. The results of this study provide important knowledge regarding the species composition of microalgae in bromeliad phytotelmata found in the Philippines. (Author's abstract)
Includes bibliographical references (pages 589-592)
Keywords: Algae; Bromeliaceae; Bromeliad tanks; Cyanobacteria; Phytotelma; Taxonomy